Effect of astragalus on characteristics of asphalt concrete - Kuloglu, N (Asce-Amer Soc Civil Engineers, 1999)
In this work, the effects of the addition of a plant gum, named Astragalus (AS), grown commonly in Central and East Anatolia, Iran, Turkmenistan, and Transkafkasia, on the stability and flow characteristics of asphalt concrete were studied. This material was mixed with asphalt cement in various proportions up to 5%. The relevant measurements were undertaken on the Marshall samples prepared using this mixture and aggregate. It was found that by mixing AS by 2%, a 59% increase instability could be achieved in comparison with the bitumen without this additive, while considerable increases in the flow values of the asphalt concrete samples, which were still between the acceptable standard limits, were observed with this amount of AS.